GİRİŞİMCİLİĞİN FİNANSMANINDA MELEK SERMAYE VE TÜRKİYE UYGULAMASI - (:unkn) unknown (My University, 2016)
Dünya'da uzun bir geçmişe sahip olan, Türkiye'de ise çok yeni ve sınırlı uygulaması bulunan melek sermaye yoluyla başarılı girişimcilik faaliyetleri gün geçtikçe artmaktadır. Melek sermayedarlar varlıklı bireyler olup, işletmede özsermaye şeklinde yer almakta; aynı zamanda girişimcilik faaliyetlerindeki deneyimleriyle danışmanlık da sağlamaktadırlar. Yüksek risk ve büyüme potansiyeline sahip firmalara yatırım yapan ve kendi bilgi birikimleriyle girişimcilere samimi destek sağlayan özel bir yatırımcı tipi olarak tanımlanan melek yatırımcı, yirmibirinci yüzyılın başlarında girişimcilik finansmanında önemli rol üstlenmiştir. Girişimciler ihtiyaç duyduklarında tavsiye ve geri bildirimlerle girişimcilik faaliyetlerine önemli ölçüde katkı sağlayan bu başarılı kişileri, melekler şeklinde de adlandırmaktadır. Girişimcilik faaliyetlerinin hayat bulması ve geliştirilmesinde mühim bir yeri olan melek sermaye aynı zamanda ekonomik kalkınmaya da katkı sağlamaktadır. Çalışmada girişim ve girişimcilik, girişimcilik finansmanı ve melek sermaye üzerine bir araştırma yer almaktadır. Az ama gittikçe artan sayıda olan melek yatırımcıların ve girişimcilerin Türkiye'deki uygulamaları, mevcut yönleriyle katkıları ortaya konmaya çalışılmaktadır

Successful entrepreneurship activity through angel capital that has a long history around the world, is increasing in Turkey day by day although it is new and limited. Angel investors while being wealthy people who take place in an enterprise as core capital, they also supply counsel providing their experience gained from their entrepreneurship activities. Entrepreneurs call these successful people angels because when they are in need, angels give them feedback and contribute to their entrepreneurship significantly. An angel investor is known as one kind of private investor who invests in firms that have a high risk but a high potential to grow. On the other hand, angel investors who provide friendly support with their own experience to entrepreneurs, play a significant role in entrepreneurial finance today. They help entrepreneurship exist and improve significantly while contributing to economic development. The use of this financing method that the usage in the United States and other countries is spreading rapidly, is also increasing steadily in Turkey. Today, we often hear that many of the world-famous firms prefer angel capital financing. This study features initiative and entrepreneurship, entrepreneurial finance and research on angel capital financing. The results of the implementation of a small but growing number of entrepreneurs and angel investors in Turkey are shown in this study with their current direction and contributions
ANGEL CAPITAL AND APPLICATIONS IN TURKEY